Analysis of Raw Material Supply System at Cv. X - Ananda Putri Haniyah; Sumaryanto Sumaryanto (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2023)
This study aims to determine the procedures for managing raw material inventory to support the smooth production process applied to CV. X. This research used a descriptive qualitative research method with a case study approach. Researchers took an object in the wood products industry, namely CV. X, which is located on Jl. Imogiri, Sumber Agung, Jetis, Bantul, Special Region of Yogyakarta 55781. This research was conducted on 28 December 2022 - 19 January 2023. Data collection techniques used in this study were interviews and observation. The analysis technique of this research uses thematic analysis techniques in data analysis of raw material supply systems. Data analysis in this study used the Atlas.ti 22 application. The research results produced the process of supplying raw materials at CV. X begins with preparing reports for raw material inventories addressed to suppliers through reports on raw material requirements, raw material stocks in warehouses, plans for purchasing raw materials, types of raw materials, and quantities and expiration dates. The production system will request raw materials from the warehouse department, and then the warehouse department will record the expenditure and condition of the raw materials in the warehouse. After that, it will be reported to the purchasing department, and the purchasing department will make submissions for the procurement of goods.